The effect of faultline and incentive schemes on knowledge-sharing behaviour - Adi, Maria Paramastri Hayuning; Nahartyo, Ertambang (Emerald Publishing, 2022)
Purpose: This study aims to examine the effect of faultline based on job responsibility and their interaction with the incentive scheme on knowledge-sharing behavior. Design/methodology/approach: This research is an experimental study with a 2 × 2 factorial design between subjects. Faultline and incentive schemes are manipulated into two groups (strong faultline–weak faultline and group incentive–individual incentives). This study involved 89 undergraduate accounting students as participants. Findings: This research shows that a strong faultline created a strong social identity effect. Hence, the knowledge-sharing behavior among group members tends to be lower than the weak faultline. Knowledge-sharing behavior tends to be higher in group incentive schemes than individual ones. However, there is no support for interactions between incentive schemes and faultline effects on knowledge-sharing behavior. The results indicate that forming a working subgroup based on informational characteristics attributes reduces cooperative behavior and knowledge sharing between groups. Originality/value: This study adds a new addition to faultline literature by examining the effect of faultline and incentive schemes on knowledge-sharing behavior based on informational characteristics attributes. Previous research on faultline and knowledge sharing was limited and primarily focused on faultlines created by demographic attributes. This study also enriches faultline literature on knowledge-sharing behavior using an experimental design. © 2022, Emerald Publishing Limited.